The impact of directly acting antivirals on the enzymatic liver function of liver transplant recipients with recurrent hepatitis C. Issue 6 (1st November 2016) - Raschzok, Nathanael; Schott, Eckart; Reutzel‐Selke, Anja; Damrah, Iman; Gül‐Klein, Safak; Strücker, Benjamin; Sauer, Igor Maximilian; Pratschke, Johann; Eurich, Dennis; Stockmann, Martin
Abstract: Background: The new directly acting antivirals (DAAs) enable all‐oral interferon‐free treatment of chronic hepatitis C virus (HCV) infection. We here investigated the effect of DAAs on the enzymatic liver function of liver transplant recipients with recurrent hepatitis C. Methods: Twenty‐one patients with elevated liver enzymes or advanced fibrosis/compensated cirrhosis caused by recurrent HCV were treated with sofosbuvir either in combination with simeprevir, or in combination with ribavirin or daclatasvir with or without ribavirin for 12 weeks. Biochemical parameters, tacrolimus trough levels, and the maximal liver function capacity (LiMAx) were measured monthly during the treatment and 12 weeks after the end of treatment. Results: All patients achieved sustained virological response 12 weeks after the end of the treatment. The transaminases and cholestasis parameters normalized until week 8 of treatment. The mean LiMAx (normal ranges >315 μg/kg/h) increased from 344±142 μg/kg/h before treatment to 458±170 μg/kg/h ( P <.0001) at the 12‐week follow‐up. In parallel, the tacrolimus trough level to dose ratio decreased from 4.68 down to 2.72 ( P =.0004). Conclusion: Antiviral treatment with DAAs enabled sustained elimination of recurrent HCV in liver transplant recipients and was associated with a significant improvement of the enzymatic liver function.